POLITICAL PROCESSES IN DASHTI-KIPCHOK IN THE 15TH-16TH CENTURIES (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2025)
It was to some extent connected with the political and ethnocultural processes that took place in the Dashti-Kipchak in the 15th and 16th centuries, and was related to which clan leaders took which land as their share (syurkol) or similar political and military processes.